Development and evaluation of a nutrition education programme for adults with type 2 diabetes mellitus in a resource limited setting of the Moretele sub-district, North West Province (South Africa) - Rheeder, Paul (University of Pretoria, 2013)
Thesis (Phd)--University of Pretoria, 2013.